Pengaruh Fasilitas Kerja, Pengembangan Karir dan Pengawasan Kerja Terhadap Kinerja Pegawai di Kantor Pelayanan Pajak Pratama - Muhammad Ridwan; Tengku Apriansya Ramadhan; Robby Barat; Ismail Arif Panjaitan; Eddi Suprayitno; Effendi Sadly; Sri Gustina Pane (TIN: Terapan Informatika Nusantara, 2023)
This study aims to determine the Effect of work facilities, career development and work supervision partially and simultaneously on the performance of employees work in the Kantor Pelayanan Pajak Pratama Medan Belawan. The study was conducted at the Kantor Pelayanan Pajak Pratama Medan Belawan Jalan Sukamulia Nomor 17A Medan, with a population of 106 people, and a study sample. of 96 people. The data analysis technique used is multiple regression analysis using the IMB Statistics computer program for Product and Service Solution (SPSS) version 24. Based on the analysis results obtained work facilities have a positive and significant effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Belawan, this is supported by the results of t count analysis > t-table (4,860 > 1,986) at n = 96 at 95% significance level. Career development has a not effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Belawan, this is supported by an analysis of t count > t-table (3,297 > 1,986) at n = 96 at 95% significance level. Work supervision has a effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Belawan, this is supported by an analysis of t count >-table (5,133 > 1,986) at n = 96 with a significant level of 95%.Value of F-count> F table (46,513 > 2,70) This states that together (multiple) there are positive and significant effects of work facilities, career development and work supervision on the performance of employees work of employees of the Kantor Pelayanan Pajak Pratama Medan Belawan. Thus the hypothesis proposed is accepted by the truth